Pembelajaran interaktif dalam meningkatkan motivasi belajar siswa sekolah dasar - Baharuddin; Putri, Lailatul Fitriah Eka; Rosulinawati (Program Studi Magister Pendidikan Agama Islam, 2024)
The aim of this research is to analyze increasing elementary school students' learning motivation through interactive learning. The research method used is descriptive qualitative. Research data collection techniques use interview instruments, observation and documentation. Data analysis techniques include data reduction, data display, and conclusion drawing/verification. The triangulation method is used to check the validity of the data. The research results show that interactive learning can increase elementary school students' learning motivation. The interactive learning strategy is applied to three components, namely the presentation of learning materials that are able to build interaction patterns between teachers, students and learning materials, the selection of learning methods that stimulate student activity and creativity, and learning media and resources that are able to attract students' attention to participate in learning. Abstrak Tujuan penelitian ini untuk menganalisis peningkatan motivasi belajar siswa sekolah dasar melalui pembelajaran interaktif. Metode penelitian yang digunakan adalah kualitatif deskriptif. Teknik pengumpulan data penelitian menggunakan instrumen wawancara, observasi, dan dokumentasi. Teknik analisis data, meliputi data reduction, data display, dan conclusion drawing/verification. Triangulasi metode digunakan untuk memeriksa keabsahan data. Hasil penelitian menunjukkan pembelajaran interaktif dapat meningkatkan motivasi belajar Siswa Sekolah Dasar. Strategi pembelajaran interaktif diterapkan pada tiga komponen, yaitu penyajian materi pembelajaran yang mampu membangun pola interaksi antara guru, siswa, dan bahan pembelajaran, pemilihan metode pembelajaran yang menstimulasi aktivitas dan kreativitas siswa, serta media dan sumber belajar yang mampu menarik perhatian siswa untuk mengikuti pembelajaran.